Chrétien de Troyes, Filomena. Trad., ed., notas y est. introd. de José Ramón Trujillo y Elisa Borsari. Iberoamericana-Vervuert, Madrid-Frankfurt/M., 2023; 172 pp. (Medievalia Hispánica, 40). - Luna Mariscal, Karla Xiomara (Nueva Revista de Filología Hispánica (NRFH), 2025)
Es una reseña